Determinants of Tax Compliance Intention on Pre-Service Tax Payer with Extended Theory of Planned Behavior - Della Fadhilatunisa; Shera Afidatunisa; Rosidah; M. Miftach Fakhri (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This study investigates the determinants of tax compliance intention among pre-service taxpayers using an extended Theory of Planned Behavior (TPB) framework. Integrating attitudes towards tax compliance (ATC), subjective norms (SN), and perceived ease with tax laws (PETX) enhances the traditional TPB model's predictive power. Data collected via a survey of pre-service taxpayers and analyzed with structural equation modeling (SEM) reveal that ATC significantly enhances tax awareness (TA) with a path coefficient of 0.397 (p < 0.001), while SN and PETX also positively affect TA with path coefficients of 0.293 (p < 0.001) and 0.195 (p < 0.001), respectively. ATC and PETX show significant direct effects on tax compliance behavior (TCB), with total effects of 0.399 (p < 0.001) and 0.403 (p < 0.001). Although SN does not directly affect TCB, its indirect effect through TA (0.082, p < 0.05) is significant. TA significantly impacts tax compliance (TC) with a path coefficient of 0.277 (p < 0.001). These results suggest that enhancing positive attitudes towards tax compliance, leveraging social norms, and simplifying tax laws are crucial for increasing tax awareness and compliance among pre-service taxpayers. The study offers valuable insights for policymakers and tax authorities to develop effective educational and regulatory strategies aimed at fostering voluntary tax compliance, contributing to the literature by validating the extended TPB model and emphasizing early intervention in tax education.